Interventional Effect of Nanosilver Paint on Fungal Load of Indoor Air in a Hospital Ward - Nasrin Rostami; Hossein Alidadi; Hossein Zarrinfar; Damon Ketabi; Hamed Tabesh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Hospital ward environments contain various types of microorganisms, in which fungal agents are one of the main contaminants that may cause hospital-acquired infections. Regarding this, the aim of the present study was to evaluate the effect of nanosilver paint on reducing fungal contaminants of indoor air in an educational, research, and treatment center. Two rooms in the hematology ward were selected. One room was painted using usual paint (control room) and the other room was painted with paint containing nanosilver particles (experimental room). One hundred and twelve samples were collected using active (Anderson BioSampler) and passive (settle plate or open plate) air sampling techniques. The samples were incubated for 3–7 days at 35°C, and the positive fungal cultures were examined according to morphological and microscopic characteristics. Following active sampling, the mean and standard deviation of the number of colony-forming units (CFU/m3) of fungi colonies in the experimental and control rooms were 29.21 ± 17.99 and 22.50 ± 10.02 before intervention and 13.79 ± 6.20 and 31.07 ± 21.1 after intervention, respectively. Following passive sampling, the number of CFU/plate in the experimental and control rooms was 6 and 0 before and 1and 1 after intervention, respectively. The use of the nanosilver paint was effective in reducing air fungal contamination. Moreover, the active sampling method was more sensitive to measuring the concentration changes for fungal bioaerosols.